Combining gradient structure and TRIP effect to produce austenite stainless steel with high strength and ductility. (15th June 2016) - Wu, X.L.; Yang, M.X.; Yuan, F.P.; Chen, L.; Zhu, Y.T.
Abstract: We report a design strategy to combine the benefits from both gradient structure and transformation-induced plasticity (TRIP). The resultant TRIP-gradient steel takes advantage of both mechanisms, allowing strain hardening to last to a larger plastic strain. 304 stainless steel sheets were treated by surface mechanical attrition to synthesize gradient structure with a central coarse-grained layer sandwiched between two grain-size gradient layers. The gradient layer is composed of submicron-sized parallelepiped austenite domains separated by intersecting ε-martensite plates, with increasing domain size along the depth. Significant microhardness heterogeneity exists not only macroscopically between the soft coarse-grained core and the hard gradient layers, but also microscopically between the austenite domain and ε-martensite walls. During tensile testing, the gradient structure causes strain partitioning, which evolves with applied strain, and lasts to large strains. The γ → α′ martensitic transformation is triggered successively with an increase of the applied strain and flow stress. Importantly, the gradient structure prolongs the TRIP effect to large plastic strains. As a result, the gradient structure in the 304 stainless steel provides a new route towards a good combination of high strength and ductility, via the co-operation of both the dynamic strain partitioning and TRIP effect. Graphical abstract: